Precise oculocentric mapping of transcranial magnetic stimulation-evoked phosphenes. Issue 11 (22nd June 2021) - Silva, Andrew E.; Tsang, Katelyn; Hasan, Syeda Javeria; Thompson, Benjamin
Abstract : Objective: Transcranial magnetic stimulation (TMS)–evoked phosphenes are oculocentric; their perceived location depends upon eye position. We investigated the accuracy and precision of TMS-evoked phosphene oculocentric mapping. Methods: We evoked central phosphenes by stimulating early visual cortical areas with TMS, systematically examining the effect of eye position by asking participants to report the location of the evoked phosphene. We tested whether any systematic differences in the precision or accuracy of responses occurred as a function of eye position. Results: Perceived phosphene locations map veridically to eye position, although there are considerable individual differences in the reliability of this mapping. Conclusions: Our results emphasize the need to carefully control eye movements when carrying out phosphene localization studies and suggest that individual differences in the reliability of the reported position of individual phosphenes must be considered.